An in-vitro comparative study of the binding of caspofungin and micafungin to plasma proteins. (16th November 2021) - Yamasaki, Keishi; Sakurama, Keiki; Nishi, Koji; Tsukigawa, Kenji; Seo, Hakaru; Otagiri, Masaki; Taguchi, Kazuaki
Abstract: Objectives: Echinocandins are widely used for the treatment of invasive fungal diseases. While they bind strongly to plasma proteins, our knowledge of this process is not sufficient to permit their pharmacokinetics and pharmacodynamics targets to be discussed. In this study, we characterized the binding of two echinocandins, caspofungin and micafungin, to plasma proteins, human serum albumin (HSA) and human α 1 -acid glycoprotein (AAG). Methods: The binding parameters, number of binding sites ( n ) and association constant ( K ) for caspofungin and micafungin to HSA and AAG were determined by equilibrium dialysis. The binding site on HSA for these echinocandins was identified by conducting inhibition experiments. Key findings: Caspofungin was found to bind strongly to a single site on HSA ( n = 1.26, K = 0.45 × 10 6 M −1 ) and AAG ( n = 0.99, K = 0.29 × 10 6 M −1 ). Micafungin was found to bind more strongly to HSA ( n = 1.35, K = 1.44 × 10 6 M −1 ) and AAG ( n = 1.32, K = 1.16 × 10 6 M −1 ). The binding site for these drugs on HSA appears to be within subdomain IA. Conclusions: Free fraction of caspofungin and micafungin in patients may not be substantially affected due to the contribution of AAG to the overall protein binding and the binding to subdomain IA on HSA, which is different from the major drug-binding sites within subdomains IB, IIA and IIIA.